Optimized preoperative fasting times decrease ketone body concentration and stabilize mean arterial blood pressure during induction of anesthesia in children younger than 36 months: a prospective observational cohort study. Issue 8 (13th June 2016) - Dennhardt, Nils; Beck, Christiane; Huber, Dirk; Sander, Bjoern; Boehne, Martin; Boethig, Dietmar; Leffler, Andreas; Sümpelmann, Robert
Summary: Background: In pediatric anesthesia, preoperative fasting guidelines are still often exceeded. Objective: The objective of this noninterventional clinical observational cohort study was to evaluate the effect of an optimized preoperative fasting management (OPT) on glucose concentration, ketone bodies, acid–base balance, and change in mean arterial blood pressure (MAP) during induction of anesthesia in children. Methods: Children aged 0–36 months scheduled for elective surgery with OPT ( n = 50) were compared with peers studied before optimizing preoperative fasting time (OLD) ( n = 50) who were matched for weight, age, and height. Results: In children with OPT ( n = 50), mean fasting time (6.0 ± 1.9 h vs 8.5 ± 3.5 h, P < 0.001), deviation from guideline (ΔGL) (1.2 ± 1.4 h vs 3.7 ± 3.1 h, P < 0.001, ΔGL>2 h 8% vs 70%), ketone bodies (0.2 ± 0.2 mmol·l −1 vs 0.6 ± 0.6 mmol·l −1, P < 0.001), and incidence of hypotension (MAP <40 mmHg, 0 vs 5, P = 0.022) were statistically significantly lower and MAP after induction was statistically significantly higher (55.2 ± 9.5 mmHg vs 50.3 ± 9.8 mmHg, P = 0.015) as compared to children in the OLD ( n = 50) group. Glucose, lactate, bicarbonate, base excess, and anion gap did not significantly differ. Conclusion: Optimized fasting times improve the metabolic and hemodynamic condition during induction of anesthesia in children younger than 36 months of age. Abstract :